Monograph: Language and Writing: Introduction to language development. (Journal of Parents and Teachers, 2013)
The monograph starts doing a reflection about the maturity of the children and when is the adequate moment to teach each learning. It starts from the idea that each child has his/her own rhythm of development but that all of them follow an evolutionary pattern of development common to everyone. It provides different activities and strategies that favor the language evolution as well as observation guidelines, problems detection and pacification for intervention.
Keywords: Language; development; activities; reading; writing; education and centerfold